2007
DOI: 10.1152/ajpheart.00736.2007
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxant action of 17β-estradiol in rat uterine arteries: role of nitric oxide synthases and estrogen receptors

Abstract: The uterine vasculature plays an important role during pregnancy by providing adequate perfusion of the maternal-fetal interface. To this end, substantial remodeling of the uterine vasculature occurs with consequent changes in responsiveness to contractile agents. The purpose of our study was to characterize the vasorelaxant effects of estrogens on vascular smooth muscles of the rat uterine artery during pregnancy and to evaluate the involvement of estrogen receptors (ESR) and nitric oxide synthases (NOS). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 50 publications
7
39
0
1
Order By: Relevance
“…This reduced sensitivity to E 2 in larger arteries is in agreement with findings of others (Lindsey et al 2011). Furthermore, the differential sensitivities to E 2 of the mesenteric, renal, and uterine arteries observed in this study are similar to values reported by others (Naderali et al 1999, Leung et al 2005, Scott et al 2007 Previous studies have shown that in vivo administration of the nonselective ER antagonist ICI 182 780 into one uterine artery of ovariectomized and E 2 -treated nonpregnant sheep blunted the E 2 effect on uterine blood flow, confirming its ER dependence (Magness et al 2005). Here, we show that ICI 182 780 resulted in a significant rightward shift in the CRCs to E 4 and E 2 , suggesting the contribution of ER.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This reduced sensitivity to E 2 in larger arteries is in agreement with findings of others (Lindsey et al 2011). Furthermore, the differential sensitivities to E 2 of the mesenteric, renal, and uterine arteries observed in this study are similar to values reported by others (Naderali et al 1999, Leung et al 2005, Scott et al 2007 Previous studies have shown that in vivo administration of the nonselective ER antagonist ICI 182 780 into one uterine artery of ovariectomized and E 2 -treated nonpregnant sheep blunted the E 2 effect on uterine blood flow, confirming its ER dependence (Magness et al 2005). Here, we show that ICI 182 780 resulted in a significant rightward shift in the CRCs to E 4 and E 2 , suggesting the contribution of ER.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we show that ICI 182 780 resulted in a significant rightward shift in the CRCs to E 4 and E 2 , suggesting the contribution of ER. However, E 2 -mediated relaxing responses were not inhibited by ICI 182 780 in endothelium-denuded rat uterine arteries (Scott et al 2007), most likely because the endothelial layer, which expresses ERs, had been mechanically removed. In vitro studies showed that ERa are localized in caveolae in isolated endothelial cells (Chambliss et al 2000), supporting the conclusion that the lack of inhibitory effect of ICI 182 780 in denuded uterine arteries was due to the mechanical removal of the endothelial layer.…”
Section: Discussionmentioning
confidence: 93%
“…For example, administration of estradiol increased estrogen receptors within 48 h in cyclic ewes [11]. Furthermore, a non-genomic pathway with a more rapid response that does not involve the synthesis of new proteins has been proposed [12]. In that regard, uterine blood flow increased 30 min after intra-arterial estradiol administration in oophorectomized ewes [13].…”
mentioning
confidence: 99%
“…In that regard, uterine blood flow increased 30 min after intra-arterial estradiol administration in oophorectomized ewes [13]. The rapid vasodilatory effect of estrogen was attributed to its direct action on vascular smooth muscle cells or to endothelial cell activation [12] with subsequent release of nitric oxide (NO) [14].Nitric oxide, a volatile gas, is a potent vasodilator [15] and the main mediator for estrogen-induced stimulation of uterine blood flow. However, it may also have estrogen-independent actions [16,17].…”
mentioning
confidence: 99%
“…It depends presumably both on a reduction in oxidative stress leading to an increased bioavailability of NO and an increased responsiveness of the vascular smooth muscle cells to vasodilator stimuli [76][77][78][79] (Figure 1). Rowland et al (1994) reported that 418 women with high exposure to mercury (i.e., female dental assistants) were less fertile than unexposed controls [80].…”
Section: Estrogenmentioning
confidence: 99%